2021
DOI: 10.47191/afmj/v6i7.05
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Effect of Direct and Indirect Taxation Revenue on Economic Growth of Nigeria

Abstract: The study was conducted to comparatively analyse the effects of direct and indirect taxation revenue on economic growth of Nigeria. This was necessitated by the revenue shortfall from Crude oil sales which has been the main revenue earner of the government and the latent potentials of taxation as the most reliable source of revenue. The study was designed to find out which of the tax category affect economic growth most in Nigeria. Ex post facto research design was the research design involving secondary data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Gale (2014) posits that a nation's tax system determines the extent of its economic growth. This corroborates Etim, Nsima, Austin, Samuel and Anselem, (2021) who noted that taxation plays a crucial role in the economic growth of the nations, adding that this benefit of taxes is yet to be harnessed among many developing countries. This implies that the payment of taxes by individuals and companies usually impacts the level of economic activities in the country, including productivity, consumption, the propensity to save and invest, and the expenditure side of the government.…”
Section: Introductionsupporting
confidence: 86%
“…Gale (2014) posits that a nation's tax system determines the extent of its economic growth. This corroborates Etim, Nsima, Austin, Samuel and Anselem, (2021) who noted that taxation plays a crucial role in the economic growth of the nations, adding that this benefit of taxes is yet to be harnessed among many developing countries. This implies that the payment of taxes by individuals and companies usually impacts the level of economic activities in the country, including productivity, consumption, the propensity to save and invest, and the expenditure side of the government.…”
Section: Introductionsupporting
confidence: 86%
“…However, under the neoclassical paradigm, taxes imposed by the government might impact development during the transition to a new stable state if they change the rate of savings and, as a result, the level of investment (Maganya 2020). Other economists expanded the idea further, such as Domar (1957), who developed the Harrod-Domar model, which adds the rate of savings in an economy as one of the long-run factors of the growth rate (Etim et al 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Interestingly, most of the studies on the VAT-economic growth relation reported mixed outcomes. Some research found a negative influence of VAT on economic growth (Adefolake & Omodero, 2022;Bank-Ola, 2021;John & Dickson, 2020), while others established a positive effect of VAT on growth in Nigeria (Adebisi et al, 2020;Adejare, 2015;Adeusi et al, 2020;Etim et al, 2021).…”
Section: Yearsmentioning
confidence: 99%